The Modern Spider Web in the Art Museum. (2nd October 2018) - Kuryłek, Dominik
Abstract: In an edited version of the catalog essay for Magdalena Abakanowicz at the Muzeum Narodowyn w Kraków (National Museum), Poland, June 19–August 29, 2010, I open with a discussion of The Round Abakan (1967), the symbolic center of the National Museum exhibition. The viewer can put his/her whole body into "penetrating" the work. The exhibition, like the artist's other presentations to date—as a whole work in itself, an allegorical construction—is a "Gesamkunstwerk" of sorts. Unlike the modern museum, which establishes a symbolic order, Abakanowicz prompts us to co-establish one. Abakanowicz invites the viewer to dialogue. To negotiate. Her art turns out to disperse the modern frameworks it is normally presented in. Tangled up in the museum like a spider web, her work simultaneously represents and conceals the form it finds itself in.